Discussing pottery standards – an everlasting story? Proposal of a basic recording system for African ceramics - Jesse, Friederike; Nowotnick, Ulrike (Journal of Global Archaeology, 2022)
We present here a recording scheme for archaeological ceramics in Africa. This is an outcome of workshop discussions within the priority program Entangled Africa and is put up as methodological report for further discussion. It is hoped that other projects will be interested in expanding its data with further materials and thus contribute to a broader interdisciplinary exchange on African pottery.